Treatment Outcome of Reconstruction for Isolated Posterior Cruciate Injury: Subjective and Objective Evaluations - Ochiai, Satoshi; Hagino, Tetsuo; Senga, Shinya; Yamashita, Takashi; Haro, Hirotaka (The Journal of Knee Surgery, 2019)
There is no consensus regarding the treatment method and outcome of posterior cruciate ligament (PCL) injury. We hypothesized that although the outcome of PCL reconstruction was favorable in terms of knee stability, the outcome was unsatisfactory in terms of patient-based assessments. The purpose of this study is to evaluate the treatment outcomes of knees that underwent reconstruction for PCL injury by subjective and objective assessments, and to analyze the correlation between various assessments. Twenty-three patients who underwent PCL reconstruction were studied. All reconstructions were performed arthroscopically by the single-bundle technique using a hamstring tendon autograft. Patients were evaluated clinically before operation and 24 months after operation using the 36-Item Short Form Health Survey (SF-36) which is a patient-based health assessment survey, Lysholm score, tibial translation ratio, Visual Analogue Scale (VAS) for pain, and range of motion (ROM) in the knee. The correlation of these assessment methods was analyzed. For the SF-36 survey, significant improvement was observed after operation in only 3 of 7 subscales compared with before surgery. Furthermore, the scores reached the national standard scores in only 3 subscales. While the Lysholm score and tibial translation ratio were improved significantly, no significant improvement in the VAS pain score was observed. For ROM assessment, approximately 30% of the patients had flexion restriction after operation, and the degree of restriction correlated positively with the VAS score. The present results indicated that although the outcome of PCL reconstruction was favorable in terms of knee stability and motor function, the outcome was unsatisfactory in terms of patient-based assessments. Since pain associated with flexion restriction appears to be a poor prognostic factor and there is a dissociation between subjective and objective assessments, improvement of the surgical method is necessary.
Keywords: posterior cruciate ligament; PCL reconstruction; treatment outcome; subjective; objective